Youth development assets: exploring environmental and psychological factors influencing youth agro-entrepreneur development in Kuala Terengganu - Nur Iva Ilyana Mohamad Najid; Siti Hajar Kamaruddin; Nur Jannah Jamil; Rusyda Helma Mohd; Nor Aizal Akmal Rohaizad (Penerbit Universiti Kebangsaan Malaysia, 2024)
Agro-entrepreneurship is not solely focused on agriculture but also covers livestock, fisheries, crops, and the food industry. The government has implemented various programmes and initiatives towards agro-entrepreneurship. Youth involvement in this field is still perceived to be of low level; however, youth development assets are yet to be explored. This study will explore youth development assets from environmental and psychological factors that contribute towards youth involvement in agro-entrepreneurship by using a descriptive qualitative research design, and data collection involves semi-structured interviews. Sample selection was done with purposive sampling techniques based on expectations about the young entrepreneurs who could participate in this study. A total of five respondents from the Kuala Terengganu Young Agropreneur Programme were involved in this study. The results from this study show that there are two youth development assets that contribute towards the involvement of young agropreneurs in the field of agro-entrepreneurship, namely internal assets (positive identity, positive values, and commitment to learning) and external assets (support from family, peers, programme implementers, and the influence of entrepreneurial networks). Through the results of this study, it has been found that youth require support from areas such as families and various parties to increase involvement in the field of agro-entrepreneurship. Recommendations for future research are also stated through the writing of this article.